(untitled) (Studia Prawnicze / The Legal Studies, 2016)
Urzeczywistnienie sprawiedliwości jest centralnym i najbardziej charakterystycznym zadaniem prawa. Gustav Radbruch definiował prawo jako zasady, które są kształtowane w tym celu, by służyły sprawiedliwości. Jednak w toku codziennego stosowania prawa organy władzy publicznej rzadko pojmują sprawiedliwość jako cel ich działań; najczęściej pierwszoplanowe znaczenie nadaje się „właściwemu” zakresowi skodyfikowanych norm prawnych. Częściej zdarza się, że sprawiedliwość jest przedmiotem nauki, w tym nauki prawa jako dyscypliny badawczej. Taki przypadek miał miejsce przy okazji opracowywania ReNEU-AL Modelu kodeksu postępowania administracyjnego Unii Europejskiej przez Grupę Naukowo-Badawczą ds. Prawa Administracyjnego Unii Europejskiej (Research Network on EU Administrative Law). The subject of the article this paper is the theoretical analysis of the concept of procedural fairness, as well as analysis of the dogmatic institutions contained in ReNEUAL Model Code of Administrative Procedure of the European Union. The aim of the pape ris the verification of the thesis that ReNEUAL proposes a procedure which allows to issue a decision which will fullfill of the principles of procedural fairness. The results of the analisysy indicate the given project respects to the greatest possible extent, in the area of issuing the decision, the principle of procedural fairness. The creators of the project – representatives of the doctrine of administrative law of the Member States of the EU – understand the concept of fair preparation of the decision in the proceedings, which is described in the Book III of the Model. on the one hand, as a high standards of protection of individual rights, and on the other, as the guarantee of effectiveness, efficiency and orientation to the public service in the field of administrative bodies. Creators of the project gathered, systematised and perfected in the draft of the Code of Administrative Procedure of the Union previously developed standards of administrative procedures of the Member States. In the case of multiple solutions ReNEUAL is innovative.